Method for preparing high-quality titanium protection layer through anode pre-dissolution coupling alternate electrolysis

Through the anode pre-dissolved coupling alternating electrolysis method, the problem of insufficient density and flatness in the preparation of complex shapes of titanium steel composites and conventional electroplating processes is solved, and the binding force, density and surface flatness of the titanium protective layer are significantly improved.

CN119710848APending Publication Date: 2025-03-28SOUTHERN MARINE SCI & ENG GUANGDONG LAB (ZHUHAI) +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411821310.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

It is difficult to prepare titanium steel composite materials with complex shapes because of the existing titanium steel composite materials, and conventional constant current or constant voltage electroplating titanium process leads to poor density and surface flatness of the titanium protective layer.

Method used

Anode pre-dissolving and coupling alternating electrolysis are used to form a high-quality titanium protective layer by performing anode pre-dissolving and positive and negative alternating electrolysis in the molten halide salt. The method includes pre-dissolving anode on the surface of the steel member, increasing the surface roughness, and forming a dense and flat titanium protective layer by alternating electrolysis of forward constant potential and reverse constant current.

Benefits of technology

The bonding force, density and surface flatness of the titanium protective layer are significantly improved, and the problem of insufficient density and flatness in the preparation of complex shapes of titanium steel composites and conventional electroplating processes is solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710848A_ABST
    Figure CN119710848A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a high-quality titanium protection layer through anode pre-dissolution coupling alternate electrolysis, and belongs to the field of surface engineering. Comprising the following steps: step 1, carrying out constant-current electrolysis in halide molten salt by taking a steel piece as an anode and titanium or iron as a cathode; step 2, performing forward constant-potential electrolysis in halide molten salt containing titanium ions by taking the steel piece obtained by the treatment as a cathode, a pure titanium plate as an anode and a platinum wire as a reference electrode, then exchanging the polarity of the cathode and the anode, namely performing reverse constant-current electrolysis by taking the titanium plate as the cathode and the steel piece as the anode, and alternating the two processes to obtain the titanium-containing alloy. Positive and negative alternate electrolysis is formed until a titanium protection layer is formed on the surface of the steel part. The titanium protection layer prepared through the method has the advantages of being high in binding force, density and surface flatness, and the quality of the titanium-plated steel and iron part can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing a high-quality titanium protective layer by anode pre-dissolution coupled with alternating electrolysis, and belongs to the field of surface engineering. The method can be used to prepare a titanium protective layer with strong bonding force, high density and good surface flatness on the surface of a steel part, thereby significantly improving the service performance of the steel part. Background Art

[0002] Steel materials have excellent mechanical properties such as high strength, high melting point, good plasticity and toughness, so they are widely used in construction, transportation, manufacturing, home appliances, energy and other fields. However, steel materials have poor corrosion resistance, especially in highly corrosive fields such as ocean and chemical industry, steel materials face urgent surface strengthening needs. Titanium metal has extremely strong corrosion resistance. At the same time, its high melting point and low density make it an excellent structural material. However, the high cost of titanium metal limits its large-scale application. If titanium metal with outstanding corrosion resistance is compounded with low-cost steel materials to form a titanium-steel composite material, it can not only solve the surface strengthening problem of steel materials, but also realize the efficient release of the excellent performance of titanium metal.

[0003] At present, the preparation methods of titanium steel composite structural materials mainly include explosive composite method, hot rolling method, cold rolling method and molten salt electroplating titanium method. The explosive composite method uses the high energy generated by explosives to make titanium and steel collide at high speed in a very short time to form a strong bond. The advantage of this method is that it has high bonding strength and can manufacture large-sized titanium steel plates; but there are problems such as manufacturing noise and vibration, requiring specific sites and strict safety control. In addition, the surface of the composite plate after the explosion is relatively rough, requiring additional surface reprocessing processes. The hot rolling method has a simple process and has the advantages of high production efficiency, continuous production, high product dimensional accuracy and uniform thickness. However, the hot rolling method consumes a lot of energy, causes great wear and tear on the equipment, and has high maintenance costs. The cold rolling method combines the titanium plate and the steel plate by rolling at room temperature, and usually requires annealing treatment. The advantage of the cold rolling method is that the process is relatively simple and the production cost is low. However, the cold rolling method is sensitive to the work hardening of the material, which may lead to a decrease in the strength and toughness of the composite plate.

[0004] In summary, the above methods have their own advantages and disadvantages and can be used to prepare titanium-steel composite materials for different purposes. However, the above three methods have a common problem, that is, they can only prepare titanium-steel composite materials with regular shapes (such as plates or a small amount of pipes). In fact, titanium-steel composite materials often involve various complex shapes in practical applications, so the titanium-steel composite preparation technology that can only produce regular shapes greatly limits the application of titanium-steel composite materials.

[0005] Relatively speaking, molten salt titanium electroplating is almost not restricted by the shape of steel parts, and titanium coatings can be electroplated on the surfaces of steel parts of various shapes. However, the conventional constant current or constant voltage titanium electroplating process has the following important challenges: First, the surface of the steel part is not clean or the surface is too smooth, which is likely to cause the bonding between the titanium coating and the steel part to be weak, thus affecting the service performance of the resulting titanium-steel composite material. Secondly, constant current or constant voltage electrolysis often leads to the large-scale generation of titanium powder, dendrites and pores, which leads to a significant reduction in the density and surface smoothness of the titanium coating, and ultimately leads to poor hardness, wear resistance and corrosion resistance of the titanium protective layer. Therefore, it is very important to improve the molten salt titanium electroplating process, optimize the electroplating parameters, and then improve the bonding between titanium and the substrate, and improve the density and surface smoothness of the titanium protective layer. Summary of the invention

[0006] Based on the above research background, the present invention proposes a method for preparing a high-quality titanium protective layer by coupling anodic pre-dissolution with alternating electrolysis. Compared with the traditional constant current or constant potential titanium electroplating process, the present invention proposes a new method for electrochemical anodic pre-dissolution roughening of steel parts, as well as a new method for positive and negative alternating electrolysis densification and flattening coupled with forward constant potential deposition and reverse constant current dissolution, and couples the two new methods into an electrolysis device and process flow. The method can not only significantly improve the bonding strength, density and flatness of the titanium protective layer on steel parts, but also has the advantages of simple process and high space utilization, and has great industrial application prospects.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] A method for preparing a high-quality titanium protective layer by anode pre-dissolution coupled with alternating electrolysis comprises the following steps:

[0009] Step 1: Perform constant current electrolysis in a halide molten salt with the steel part as an anode and titanium or iron as a cathode, thereby improving the surface roughness of the steel part;

[0010] Step 2: Using the steel part obtained by the above treatment as the cathode, the pure titanium plate as the anode, and the platinum wire as the reference electrode, forward constant potential electrolysis is carried out in a halide molten salt containing titanium ions, and then the polarity of the cathode and cathode are exchanged, that is, the titanium plate is used as the cathode and the steel part is used as the anode for reverse constant current electrolysis, and these two processes are alternated to form positive and negative alternating electrolysis until a dense and smooth titanium protective layer is formed on the surface of the steel part.

[0011] Furthermore, in the step one, the halide molten salt is a molten salt in which one or more of alkali metal and alkaline earth metal chlorides and fluorides are mixed in a eutectic ratio, and the eutectic ratio is a ratio of the eutectic point of the selected molten salt found according to the phase diagram; the electrolysis temperature in steps one and two is 50-200°C above the melting point of the selected halide molten salt.

[0012] The molten salt used in the electrolysis of the present invention is the same as the molten salt used in the conventional constant current or constant voltage titanium electroplating process in the prior art. The alkali metal chloride is selected from at least one of lithium chloride, sodium chloride, potassium chloride, cesium chloride, lithium fluoride, sodium fluoride, potassium fluoride, cesium fluoride, lithium bromide, sodium bromide, potassium bromide, cesium bromide, lithium iodide, sodium iodide, potassium iodide, and cesium iodide, and the alkaline earth metal chloride is selected from at least one of magnesium chloride, calcium chloride, strontium chloride, barium chloride, magnesium fluoride, calcium fluoride, strontium fluoride, barium fluoride, magnesium bromide, calcium bromide, strontium bromide, barium bromide, magnesium iodide, calcium iodide, strontium iodide, and barium iodide.

[0013] Furthermore, in step 1, the current density of constant current electrolysis is 0.1-1000 mA / cm 2 Between, preferably 0.01-0.1A / cm 2 The electrolysis time is determined by the amount of anode dissolution, specifically, the electrolysis time that can theoretically dissolve 1-1000 μm thickness of the steel part based on 100% current efficiency.

[0014] Furthermore, in step 2, the halide molten salt containing titanium ions is prepared by adding 0.5-10 wt% of TiCl 2 、TiCl 3 or K 2 TiF 6 Mixed halide molten salt.

[0015] Furthermore, in the step 2, the electrode potential set on the cathode of the steel part in the forward constant potential electrolysis is between -1.0 V and -2.5 V (relative to the Pt reference electrode), and the electrolysis time is between 0.1-100 s.

[0016] Furthermore, in step 2, the current density of the reverse constant current electrolysis is 0.1-1000 mA / cm 2 Between, preferably 0.1-1A / cm 2 The electrolysis time is controlled based on the electrolysis amount generated by the forward constant potential electrolysis. Specifically, the amount of reverse constant current electrolysis can only be between 1% and 10% of the amount of forward constant potential electrolysis, so as to prevent the steel parts from not being able to obtain a titanium protective layer during the alternating electrolysis. The electrolysis time in the embodiment is 1-100 s.

[0017] Furthermore, in step 2, the number of alternating positive and negative electrolysis is determined according to the thickness of the desired titanium coating. The number of alternating times and the time of each electrolysis are related to the amount of electricity passed and the current efficiency, so the number of alternating times is set according to the coating thickness. Specifically, a titanium protective layer with an average thickness of 1-1000 μm can be electroplated on the surface of the steel part.

[0018] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0019] 1) The surface of the steel part can be roughened by anodic pre-dissolution, thereby increasing the effective contact surface between the titanium coating and the steel part and the three-dimensional complexity of the contact structure, thereby significantly improving the bonding strength of the coating.

[0020] 2) Through alternating positive and negative electrolysis, the formation of large amounts of titanium powder or pores in the coating in conventional constant current or constant voltage titanium electroplating processes can be effectively suppressed, thereby greatly improving the density of the titanium protective layer on the surface of steel parts.

[0021] 3) Alternating positive and negative electrolysis can also inhibit the uncontrolled growth of titanium dendrites. The protruding dendrites can be dissolved by reverse constant current electrolysis, and the concave parts can be filled by forward constant voltage electrolysis, thereby effectively improving the surface flatness of the titanium protective layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0023] Figure 1 The present invention provides a process flow and principle schematic diagram of a method for preparing a high-quality titanium protective layer by anode pre-dissolution coupled with alternating electrolysis.

[0024] Figure 2 For conventional constant current electroplating (current density 0.1 A / cm 2 ) SEM morphology of the obtained product.

[0025] Figure 3 This is the SEM morphology of the coating obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0026] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.

[0027] Example 1

[0028] 300 g of 3 wt% TiCl 2 The NaCl-KCl (molar ratio 1:1) eutectic salt of the titanium source was added to the electrolytic cell as an electrolyte, and Ar gas was introduced for protection at 10 °C min -1 It was slowly heated to 700 °C and kept at this temperature for 3 h before being used for electrolysis.

[0029] First, a Q320 steel sheet was used as the anode and a titanium sheet was used as the cathode at 0.1 A / cm 2 Anodic pre-electrolysis was performed for 5 min at an anodic current density of 0.05 A / cm2. Subsequently, the steel sheet obtained by pre-electrolysis was used as the cathode (working electrode), the titanium sheet was used as the anode (counter electrode), and the platinum wire was used as the reference electrode. Electrolysis was performed at a constant potential of -2.2 V (relative to the platinum reference electrode) for 10 s. Then, the cathode and cathode were exchanged, that is, the steel sheet was used as the anode (working electrode) and the titanium sheet was used as the cathode (counter electrode). 2 The electrolysis was carried out at an anode current density of 1 s; then the above two steps were repeated to perform alternating positive and negative electrolysis, and the alternating cycle was repeated 300 times to obtain a Q320 steel sheet with a titanium protective layer.

[0030] Compared with the titanium protective layer obtained by conventional constant current electroplating (i.e., the product of Comparative Example 1), the titanium protective layer prepared in this embodiment has a density increased by 30%, a surface flatness increased by 40%, and a bonding strength between titanium and the substrate increased by 30%.

[0031] Example 2

[0032] 300 g of 6 wt% TiCl 2 The titanium source LiCl-KCl eutectic salt (molar ratio 58.5:41.5) was added to the electrolytic cell as an electrolyte, and Ar gas was introduced for protection at 8°C min -1 Slowly heat to 800 °C and keep warm for 2 h before using for electrolysis.

[0033] First, a Q235 steel sheet was used as the anode and a titanium sheet was used as the cathode at 0.2 A / cm 2 Anodic pre-electrolysis was performed for 2 min at an anodic current density of 0.02 A / cm2. Subsequently, the Q235 steel sheet obtained by pre-electrolysis was used as the cathode (working electrode), the titanium sheet was used as the anode (counter electrode), and the platinum wire was used as the reference electrode, and electrolysis was performed at a constant potential of -2.4 V (relative to the platinum reference electrode) for 8 s; then the cathode and cathode were exchanged, that is, the Q235 steel sheet was used as the anode (working electrode), the titanium sheet was used as the cathode (counter electrode), and the current density was 0.02 A / cm2. 2 Electrolysis was performed at an anode current density of 1 s; then the above two steps were repeated to perform alternating positive and negative electrolysis, and the alternating cycle was 500 times to obtain a Q235 steel sheet with a titanium protective layer.

[0034] Compared with the titanium protective layer obtained by conventional constant current electroplating, the titanium protective layer prepared in this embodiment has a density increased by 43%, a surface flatness increased by 54%, and a bonding strength between titanium and the substrate increased by 89%.

[0035] Example 3

[0036] 400 g of 4 wt% K 2 TiCl 6Titanium source NaCl-CaCl 2 Eutectic salt (molar ratio 49:51) was added to the electrolytic cell as electrolyte, and Ar gas was introduced for protection at 6°C min -1 Slowly heat to 900 °C and keep warm for 3 h before use in electrolysis.

[0037] First, the Q320 adapter was used as the anode and the titanium sheet was used as the cathode at 0.15 A / cm 2 Anodic pre-electrolysis was performed for 3 min at an anodic current density of 1.5 A / cm2. Subsequently, the Q320 adapter obtained by pre-electrolysis was used as the cathode (working electrode), the titanium sheet was used as the anode (counter electrode), and the platinum wire was used as the reference electrode. Electrolysis was performed at a constant potential of -2.2 V (relative to the platinum reference electrode) for 5 s. Then, the cathode and cathode were exchanged, that is, the Q320 adapter was used as the anode (working electrode), the titanium sheet was used as the cathode (counter electrode), and the current density was 0.01 A / cm2. 2 Electrolysis was performed at an anode current density of 1 s; then the above two steps were repeated to perform alternating positive and negative electrolysis, and the alternating cycle was 800 times to obtain a Q320 adapter with a titanium protective layer.

[0038] Compared with the titanium protective layer obtained by conventional constant current electroplating, the titanium protective layer prepared in this embodiment has a density increased by 36%, a surface flatness increased by 45%, and a bonding strength between titanium and the substrate increased by 87%.

[0039] Example 4

[0040] 350 g of 4 wt% TiCl 2 The titanium source NaCl-KCl-LiCl eutectic salt (molar ratio 36:36:34) was added to the electrolytic cell as an electrolyte, and N 2 Gas protection, 15 ℃ min -1 Slowly heat to 600 °C and keep warm for 1 h before using for electrolysis.

[0041] First, a 304 stainless steel sheet was used as the anode and a titanium sheet was used as the cathode at 0.3 A / cm 2 Anodic pre-electrolysis was performed for 2 min at an anodic current density of 0.02 A / cm2. Subsequently, the 304 stainless steel sheet obtained by pre-electrolysis was used as the cathode (working electrode), the titanium sheet was used as the anode (counter electrode), and the platinum wire was used as the reference electrode. Electrolysis was performed at a constant potential of -2.25 V (relative to the platinum reference electrode) for 20 s. Then, the cathode and cathode were exchanged, that is, the 304 stainless steel sheet was used as the anode (working electrode), the titanium sheet was used as the cathode (counter electrode), and the reaction was continued at 0.02 A / cm2. 2 Electrolysis was carried out at an anode current density of 3 s; then the above two steps were repeated to perform alternating positive and negative electrolysis, and the alternating cycle was 600 times to obtain a 304 stainless steel sheet with a titanium protective layer.

[0042] Compared with the titanium protective layer obtained by conventional constant current electroplating, the titanium protective layer prepared in this embodiment has a density increased by 43%, a surface flatness increased by 35%, and a bonding strength between titanium and the substrate increased by 65%.

[0043] Example 5

[0044] With 280 g of 6 wt% K 2 TiCl 6 The titanium source KCl-LiF eutectic salt (molar ratio 77:23) was added to the electrolytic cell as an electrolyte, and Ar gas was introduced for protection at 7 °C min -1 Slowly heat to 800 °C and keep warm for 2 h before using for electrolysis.

[0045] First, the Q320 nut was used as the anode and the titanium sheet was used as the cathode at 0.2 A / cm 2 Anodic pre-electrolysis was performed for 8 min at an anodic current density of 1.5 A / cm2. Subsequently, the Q320 nut obtained by pre-electrolysis was used as the cathode (working electrode), the titanium sheet was used as the anode (counter electrode), and the platinum wire was used as the reference electrode. Electrolysis was performed at a constant potential of -2.25 V (relative to the platinum reference electrode) for 12 s. Then, the cathode and cathode were exchanged, that is, the Q320 nut was used as the anode (working electrode), the titanium sheet was used as the cathode (counter electrode), and the current density was 0.03 A / cm2. 2 Electrolysis was performed at an anode current density of 2 s; then the above two steps were repeated to perform alternating positive and negative electrolysis, and the alternating cycles were repeated 350 times to obtain a Q320 nut with a titanium protective layer.

[0046] Compared with the titanium protective layer obtained by conventional constant current electroplating, the titanium protective layer prepared in this embodiment has a density increased by 54%, a surface flatness increased by 47%, and a bonding strength between titanium and the substrate increased by 58%.

[0047] Example 6

[0048] 600 g of 2 wt% TiCl 3 BaCl 2 -CaCl 2 The eutectic salt (molar ratio 38:62) was added as electrolyte to the electrolytic cell, and N 2 Gas protection, 12 ℃ min -1 Slowly heated to 750 °C and kept warm for 2 h before being used for electrolysis. First, a Q235 steel tube was used as the anode and a titanium sheet was used as the cathode at 0.15 A / cm 2Anodic pre-electrolysis was performed for 4 min at an anodic current density of 0.04 A / cm2. Subsequently, the Q235 steel tube obtained by pre-electrolysis was used as the cathode (working electrode), the titanium sheet was used as the anode (counter electrode), and the platinum wire was used as the reference electrode. Electrolysis was performed at a constant potential of -2.3 V (relative to the platinum reference electrode) for 10 s. Then, the cathode and cathode were exchanged, that is, the Q235 steel tube was used as the anode (working electrode), the titanium sheet was used as the cathode (counter electrode), and the current density was 0.04 A / cm2. 2 Electrolysis was performed at an anode current density of 1s; then the above two steps were repeated to perform alternating positive and negative electrolysis, and the alternating cycle was repeated 400 times to obtain a Q235 steel pipe with a titanium protective layer.

[0049] Compared with the titanium protective layer obtained by conventional constant current electroplating, the titanium protective layer prepared in this embodiment has a density increased by 29%, a surface flatness increased by 65%, and a bonding strength between titanium and the substrate increased by 98%.

[0050] Comparative Example 1

[0051] 300 g of 3 wt% TiCl 2 The NaCl-KCl (molar ratio 1:1) eutectic salt of the titanium source was added to the electrolytic cell as an electrolyte, and Ar gas was introduced for protection at 10 °C min -1 It was slowly heated to 700 °C and kept at this temperature for 3 h before being used for electrolysis.

[0052] With Q320 steel sheet as cathode and titanium sheet as anode, the 2 The Q320 steel sheet with a titanium protective layer was obtained by electroplating at a current density of 100 for 1 hour. Comparative Example 1 The titanium protective layer was prepared by conventional constant current electroplating, and the molten salt and electroplating temperature were the same as those in Example 1.

[0053] Figure 1 The present invention provides a process flow and principle diagram of a method for preparing a high-quality titanium protective layer by anodic pre-dissolution coupled with alternating electrolysis. Traditional methods all use direct electrodeposition, that is, a single constant potential or constant current to deposit a titanium layer. The current density and voltage during the reaction are not fixed, and anodic pre-dissolution and alternating electrolysis are not performed. The resulting coating has low bonding strength, low density, and poor surface flatness. The present invention first performs anodic pre-oxidation to roughen the surface of the plated part, so that the plated titanium can have better bonding strength with the steel part. Then, through positive and negative alternating electrolysis, the density and surface flatness of the coating can be improved.

[0054] Figure 2 For comparative example 1, conventional constant current electroplating (current density 0.1 A / cm 2 ) The morphology of the obtained product, Figure 3 The morphology of the coating obtained in Example 1. As can be seen from the figure, the method provided by the present invention significantly improves the density and surface flatness of the coating.

[0055] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a high-quality titanium protective layer by anode pre-dissolution coupled with alternating electrolysis, characterized in that: The following steps are involved: Step 1: Perform constant current electrolysis in a halide molten salt with a steel part as an anode and titanium or iron as a cathode; Step 2: Using the steel part obtained by the above treatment as the cathode, the pure titanium plate as the anode, and the platinum wire as the reference electrode, forward constant potential electrolysis is carried out in a halide molten salt containing titanium ions, and then the polarity of the cathode and cathode are exchanged, that is, the titanium plate is used as the cathode and the steel part is used as the anode for reverse constant current electrolysis, and these two processes are alternated to form positive and negative alternating electrolysis until a titanium protective layer is formed on the surface of the steel part.

2. The method for preparing a high-quality titanium protective layer by anode pre-dissolution coupled with alternating electrolysis according to claim 1, characterized in that: In the step 1, the halide molten salt is a molten salt in which one or more of alkali metal and alkaline earth metal chlorides and fluorides are mixed in a eutectic ratio; the electrolysis temperature in steps 1 and 2 is 50-200° C. above the melting point of the selected halide molten salt.

3. The method for preparing a high-quality titanium protective layer by anode pre-dissolution coupled with alternating electrolysis according to claim 1, characterized in that: In the step 1, the current density of the constant current electrolysis is 0.1-1000 mA / cm 2 , preferably 0.01-0.1A / cm 2 .

4. The method for preparing a high-quality titanium protective layer by anode pre-dissolution coupled with alternating electrolysis according to claim 3, characterized in that: In the step 1, the electrolysis time is the time for theoretically dissolving the steel piece to a thickness of 1-1000 μm, calculated based on 100% current efficiency.

5. The method for preparing a high-quality titanium protective layer by anode pre-dissolution coupled with alternating electrolysis according to claim 1, characterized in that: In the step 2, the halide molten salt containing titanium ions is: a mixed halide molten salt in which 0.5-10 wt% of TiCl2, TiCl3 or K2TiF6 is added to a molten salt in which one or more of alkali metal and alkaline earth metal chlorides and fluorides are mixed in a eutectic ratio.

6. According to the method for preparing a high-quality titanium protective layer by anodic pre-dissolution coupled with alternating electrolysis according to claim 5, in the step 2, the electrode potential set on the cathode of the steel part in the forward constant potential electrolysis is -1.0 V to -2.5 V, and the electrolysis time is 0.1-100 s.

7. The method for preparing a high-quality titanium protective layer by anode pre-dissolution coupled with alternating electrolysis according to claim 1, wherein in step 2, the current density of the reverse constant current electrolysis is 0.1-1000 mA / cm 2 , preferably 0.1-1A / cm 2 .

8. According to the method for preparing a high-quality titanium protective layer by anodic pre-dissolution coupled alternating electrolysis according to claim 7, in the step 2, the reverse constant current electrolysis time is determined according to the electrolysis amount generated by the forward constant potential electrolysis, specifically, the reverse constant current electrolysis amount is 1%-10% of the forward constant potential electrolysis amount.

9. According to the method for preparing a high-quality titanium protective layer by anodic pre-dissolution coupled alternating electrolysis according to claim 1, in the step 2, the number of alternating positive and negative alternating electrolysis is determined according to the required thickness of the titanium coating, specifically, a titanium protective layer with an average thickness of 1-1000 μm is electroplated on the surface of the steel part.